The Influence of Human Resource Quality on Job Satisfaction with Competence as an Intervening Variable (Case Study at Dr. RM. Djoelham Hospital, Binjai City) - Dahris Dahris; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of the quality of human resources on job satisfaction with competence as an intervening variable. This research was conducted in one of the general hospitals of RSUD Dr. Rom. Djoelham City of Binjai. The population in this study was 70 employees and the sample used was a saturated sample. The research model is a path analysis measuring tool using Smrat PLS 3.3.3. The results of this study are that competence has a positive and significant effect on job satisfaction. HR quality has a positive and significant effect on job satisfaction. HR quality has a positive and significant effect on competence. HR quality has a positive and significant effect on job satisfaction through competence.